The Development of Pop-Up Book Teaching and Learning Media toward the Pancasila and Civic Education Lesson Content on Students Grade Five in Elementary School - Damayanti, Putu Yuni; Putra, Made (International Journal of Elementary Education, 2021)
The availability of learning media in grade five is very lass varied, especially three-dimensional learning media which have characteristics that are suitable for elementary school students. This causes students to find it difficult to understand the subject matter and students get bored easily in the classroom. This study was aimed to find out the validity of Pop-Up Book teaching and learning media toward the Pancasila values lesson in daily life on students grade five in elementary school. This study applied Dick & Carry model consisted of eight steps. The subject in this study is Pop-Up Book. The try-out design in this study consisted of expert review for the teaching and learning content, expert review for the teaching and learning design and expert review for teaching and learning media, personal tryout, and small group tryout. The data in this development study were collected by administrating formative tests from the expert review and students. Data collection techniques in this study were observation, interviews, and questioner. Then, the data were analyzed by using qualitative descriptive technique and quantitative descriptive technique. The validity of the mean score of the teaching and learning content shown 93.18% with excellent qualification, teaching, and learning design is shown 89.28% with good qualification, the teaching and learning media shown 91.66% with an excellent qualification. Whereas personal tryout showed 95.83% and small group tryout showed 94.90%. Based on the analysis data above, this study could be concluded that the development of the Pop-Up Book Model using Dick & Carry was valid.